Can money heal all wounds? Social exchange norm modulates the preference for monetary versus social compensation - Cao, Yulong; Yu, Hongbo; Wu, Yanhong; Zhou, Xiaolin (Frontiers in Psychology, 2015)
Compensation is a kind of pro-social behavior that can restore a social relationship jeopardized by interpersonal transgression. The effectiveness of a certain compensation strategy (e.g., repaying money, sharing loss, etc.) may vary as a function of the social norm/relationship. Previous studies have shown that two types of norms (or relationships), monetary/exchange and social/communal, differentially characterize people’s appraisal of and response to social exchanges. In this study, we investigated how individual differences in preference for these norms affect individuals’ perception of others’ as well as the selection of their own reciprocal behaviors. In a two-phase experiment with interpersonal transgression, we asked the participant to perform a dot-estimation task with two partners who occasionally and unintentionally inflict noise stimulation upon the participant (first phase). As compensation one partner give money to the participant 80% of the time (the monetary partner) and the other bear the noise for the participant 80% of the time (the social partner). Results showed that the individuals’ preference for compensation (repaying money versus bearing harm) affected their relationship (exchange versus communal) with the partners adopting different compensation strategies: participants tended to form communal relationships and felt closer to the partner whose compensation strategy matched their own preference. The participants could be differentiated into a social group, who tended to form communal relationship with the social partner, and a monetary group, who tended to form communal relationship with the monetary partner. In the second phase of the experiment, when the participants became transgressors and were asked to compensate for their transgression with money, the social group offered more compensation to the social partners than to the monetary partners, while the monetary group compensated less than the social group in general and showed no difference in their offers to the monetary and social partners. These findings demonstrate that the effectiveness of compensation varies as a function of individuals’ preference for communal versus monetary norm and that monetary compensation alone does not heal all wounds.